Intercountry Adoption in Taiwan - Tsai, Hua Kai (UI Scholars Hub, 2022)
Under the current choice-of-law rule concerning the intercountry adoption in the Taiwanese Private International Law Act, the adopter and the child should be governed by their national law respectively. The application of this rule is known as a distributive approach and the rule was made by reference to the old Japanese private international law. However, in 1989, Japanese law revised the choice-of-law rule on intercountry adoption and abandoned the distributive approach, due to the reason that such an approach tended to be construed as a cumulative approach by Japanese courts. Consequently, the formation of intercountry adoption in Japan turned out to be more difficult under the application of the cumulative approach. It made the adoptive parent governed not only by his or her national law, but also by the child’s national law, and vice versa for the child. Thus, this complicated approach has become the main reason for Japan to make a law reform on intercountry adoption in 1989 amendment of private international. The same situation is happening in Taiwan. Most Taiwanese courts falsely construe the choice-of-law rule on intercountry adoption as a cumulative approach. Unfortunately, the latest amendment on intercountry adoption in the Taiwanese private law act made no substantial change to the new provision. This article also argues that the application of hidden renvoi to intercountry adoption cases is not only contradictive to the objects of the theory of renvoi but also lacks theoretical justifications in private international law methods.